Influence of inflammation on the expression of microRNA-140 in extracellular vesicles from 2D and 3D culture models of synovial-membrane-derived stem cells - Pfeifer, João Pedro Hübbe; Stievani, Fernanda de Castro; Fernandes, Célio J. da Costa; Rosa, Gustavo dos Santos; Apolonio, Emanuel Vitor Pereira; Rossi, Mariana Correa; Zambuzzi, Willian Fernando; Alves, Ana Liz Garcia (Frontiers in Bioengineering and Biotechnology, 2024)
Background: In osteoarthritis (OA), articular homeostasis is regulated, for instance, by microRNA-140, which inhibits ADAMTS-5 an enzyme that cleaves aggrecan and 2 stimulates the synthesis of other inflammatory mediators. This study aims to evaluate the expression of microRNA-140 in extracellular vesicles (EVs) derived from equine synovial membrane-derived MSCs (eqSMMSCs) cultured in monolayer (2D) and three-dimensional (3D) culture models under an in vitro inflammatory environment.Methods: Four experimental groups of eqSMMSC cultures were defined for EVs isolation. Control groups 2D and 3D were cultured in conventional cell culture medium. Treated groups 2D-OA and 3D-OA were exposed to an osteoarthritis-like medium containing IL-1β and TNFα. Culture media samples were collected at 24h, 72h, and 120h time points for EV isolation and characterized using nanoparticle tracking analysis (NTA) and transmission electron microscopy (TEM). RT-qPCR was employed to assess the expression of microRNA-140 in both cells and EVs. All statistical analyses were conducted at a significance level of 5%.Results: Encapsulation of eqSMMSCs protected cells from the inflammatory medium compared to monolayer culture. EVs were found in higher concentrations in 3D-OA cultures. Additionally, higher expression of miRNA-140 was observed in cells of the 3D-OA group at 24 and 72 hours, whereas miRNA-140 expression in EVs was higher in the 3D group at 72 hours and in the 2D-OA group at 120 hours (P < 0.001).However, 3D-OA cultures showed higher expression of mRNA Adamts5 in EVs at 120 hours.The response of eqSMMSCs to inflammatory stimuli involves intracellular expression of miRNA-140 and its subsequent transport via EVs, with a quicker response observed in 3D cultures compared to 2D cultures. This study shed light into the behavior of stem cells in restoring homeostasis in osteoarthritic joints.